2020
DOI: 10.30596/jimb.v21i2.4295
|View full text |Cite
|
Sign up to set email alerts
|

Disiplin Kerja, Pengalaman Kerja Terhadap Kepuasan Kerja dan Kinerja Pengawas

Abstract: This research aims to determine the direct and indirect influence of work discipline and work experience on job satisfaction and supervisor performance in the Education office of South Sulawesi Province. The research used is explanative with survey approach Sampling technique with simple random sampling method. The method used in this study is to use the Partial Least Square (PLS) method. From the results of the study to the direct influence shows work discipline does not affect job satisfaction, work discipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
3
0
6
Order By: Relevance
“…The results of this study are in line with the results of research conducted by previous research which states that work discipline has a positive and significant influence on employee job satisfaction (Sekartini, 2016;Yuliantini & Santoso, 2020). Furthermore, similar studies concluded that work discipline has an effect on job satisfaction (Indriati & Nazhifi, 2022;Sabirin, S. & Ilham, 2020).…”
Section: The Effect Of Work Discipline On Job Satisfactionsupporting
confidence: 91%
“…The results of this study are in line with the results of research conducted by previous research which states that work discipline has a positive and significant influence on employee job satisfaction (Sekartini, 2016;Yuliantini & Santoso, 2020). Furthermore, similar studies concluded that work discipline has an effect on job satisfaction (Indriati & Nazhifi, 2022;Sabirin, S. & Ilham, 2020).…”
Section: The Effect Of Work Discipline On Job Satisfactionsupporting
confidence: 91%
“…Because the significant level is greater than the alpha value, work discipline has an insignificant effect on job satisfaction. Meanwhile, according to Sabirin and Ilham (2020) Work discipline has no positive and significant effect on supervisor job satisfaction. The results of the study found that work discipline was not proven to have a significant effect on supervisor job satisfaction.…”
Section: Discussionmentioning
confidence: 92%
“…Hal ini sesuai dengan hasil penelitian (Thahrim, 2021) dan penelitian dari (Munir et al, 2020) yang membuktikan bahwa disiplin kerja memberikan pengaruh positif dan signifikan terhadap kepuasan pegawai. Penelitian (Sabirin & Ilham, 2020) telah membuktikan bahwa disiplin kerja memberikan pengaruh signifikan terhadap kepuasan kerja pegawai.…”
Section: Pembahasan Hipotesis Pertama (H 1 ) : Disiplin Kerja Berpeng...unclassified